2017
DOI: 10.14257/ijfgcn.2017.10.11.02
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Cognitive Radio Network using Artificial Neural Network

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…By the utilization of these networks, the utilization of current trends and current technologies will increase the usage of the Internet of Things and other technologies. The infrastructure for these networks also has to be established and forgetting the better results, and these networks should be installed and established in a more significant way [10] [11].…”
Section: About Various Latest Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…By the utilization of these networks, the utilization of current trends and current technologies will increase the usage of the Internet of Things and other technologies. The infrastructure for these networks also has to be established and forgetting the better results, and these networks should be installed and established in a more significant way [10] [11].…”
Section: About Various Latest Technologiesmentioning
confidence: 99%
“…Some of the essential topics and other issues to be studied for the better functioning and working of the current models and applications are observed as follows, Some of the essential classifications or the types of artificial intelligence models can be observed in the current day trends are like the limited memory, reactive machines, theory of mind and self-awareness. The applications and the processing of all these sorts of applications can be considered for the better understanding, and the functioning of such applications can be useful for the better results and better utilization [11]. The memory should always be useful, and the limited memory may not be sufficient.…”
Section: Artificial Intelligencementioning
confidence: 99%
“…In [128] authors have summarized a few studies on the benefit of NN network-based spectrum prediction techniques, and concluded that without needing much prior knowledge of the system, ANN shows the best performance.…”
Section: Machine Learning In Wireless Networkmentioning
confidence: 99%